Digital Literacy in Matrilineal Family - MHD Natsir; Melvina Melvina; Dafetta Fitri Linda (STKIP Singkawang, 2025)
The study aims to reveal the efforts that can be made to avoid the undesirable impact of digital technology by growing digital literacy in the matrilineal family. The development of digital information technology does not entirely have a positive impact on family social life. Reduced time with family members, increased individualism, and minimal interaction within the family are some of the negative impacts that must be anticipated. To solve this problem, a comprehensive review of the literature on matrilineal family settings is performed. Several relevant articles are collected and organized into categories. Based on the analysis, to improve digital literacy in the family, there are a few things that should be done. First, increase the parents' knowledge (father, mother, and mamak), commit to using healthy digital technology, provide a variety of fun activities, understand the norms and ethics that apply in utilizing digital technology and involve all family members to play a part in controlling the use of technology.